2022
DOI: 10.3389/fnins.2022.1017883
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic nomogram for the outcomes in acute stroke patients with intravenous thrombolysis

Abstract: Background and purposeThe prediction of neurological outcomes in ischemic stroke patients is very useful in treatment choices, as well as in post-stroke management. This study is to develop a convenient nomogram for the bedside evaluation of stroke patients with intravenous thrombolysis.Materials and methodsWe reviewed all enrolled stroke patients with intravenous thrombolysis retrospectively. Favorable outcome was defined as modified Rankin Score (mRs) less than 2 at 90 days post thrombolysis. We compared the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Radiomics can be used to identify quantitative imaging indexes, which have the advantage of non-invasiveness; a novel nomogram, including clinical features and radiomics features, was constructed to predict neurological outcomes in ischemic stroke and exhibited good performance (18). Zheng et al (19) (20). Notably, a nomogram has also been utilized to predict mortality in patients with ischemic stroke (5,6).…”
Section: Discussionmentioning
confidence: 99%
“…Radiomics can be used to identify quantitative imaging indexes, which have the advantage of non-invasiveness; a novel nomogram, including clinical features and radiomics features, was constructed to predict neurological outcomes in ischemic stroke and exhibited good performance (18). Zheng et al (19) (20). Notably, a nomogram has also been utilized to predict mortality in patients with ischemic stroke (5,6).…”
Section: Discussionmentioning
confidence: 99%
“…All prediction models were internally validated, and 26 of them were externally validated. Additionally, among the 28 eligible studies, 15 studies were multi-centered ( 27 29 , 39 , 45 , 47 , 52 , 55 , 58 64 ); five studies extracted their original data from databases ( 24 , 25 , 32 , 37 , 57 ); and the remaining 24 studies were single-centered. Most eligible studies focused on IS and 7 studies ( 23 , 32 , 39 , 40 , 48 , 60 , 63 ) on HS.…”
Section: Resultsmentioning
confidence: 99%
“…Due to distinct purposes, these included studies defined poor motor function in a different manner. Specifically, it was defined as Modified Rankin Scale >1 in 4 studies ( 26 , 31 , 45 , 58 ), Modified Rankin Scale >3 in 4 ( 39 , 53 , 60 , 63 ) studies, Modified Rankin Scale >4 in two ( 25 , 42 ) studies, and Modified Rankin Scale >2 in other 34 studies. In this study, a total of 13 primary studies using radiomics as predictive factors were identified ( 27 , 30 , 36 , 37 , 49 , 51 , 52 , 54 57 , 61 , 62 ), from which 33 prediction models were extracted.…”
Section: Resultsmentioning
confidence: 99%
“…A nomogram is a visualization method for clinical predictive models that are widely used in the eld of ischemic stroke. For example, Zheng et al [ 40] developed a simple nomogram to assess the neurological outcome of acute ischemic stroke treated with intravenous thrombolysis, and external validation demonstrated the robustness of the predictive model. Liu C et al [ 41] found that hyperglycemia was associated with poor functional prognosis of stroke and used it to construct a nomogram, which has good clinical application value in predicting the functional prognosis of stroke.…”
Section: Discussionmentioning
confidence: 99%